Curcumin Mitigates Neuro-Inflammation by Modulating Microglia Polarization Through Inhibiting TLR4 Axis Signaling Pathway Following Experimental Subarachnoid Hemorrhage - Gao, YongYue; Zhuang, Zong; Lu, Yue; Tao, Tao; Zhou, Yan; Liu, GuangJie; Wang, Han; Zhang, DingDing; Wu, LingYun; Dai, HaiBin; Li, Wei; Hang, ChunHua (Frontiers in Neuroscience, 2019)
Subarachnoid hemorrhage (SAH) elicits destruction of neuronal cells and neurological function, which is exacerbated by neuro-inflammation in EBI, and toll-like receptor 4 (TLR4) plays an important role in inflammatory cascade via modulation microglia polarization. Curcumin (Cur), as a natural phytochemical compound, has the potential characteristics on anti-inflammatory and microglia phenotype transformation. In this study, we verified the hypothesis curcumin promotes M2 polarization to inhibiting neuro-inflammation, which through suppressing TLR4 signaling pathway after SAH. In tlr4-/- mice and wild type (WT) subjected to prechiasmatic cistern blood injection, Western blotting, brain water content, neurological score, enzyme-linked immunosorbent assay (ELISA) and terminal deoxynucleotidyl transferase dUTP nick endlabeling (TUNEL) staining were performed to investigate the role of TLR4 on neuro-inflammation response and microglia polarization. Curcumin with three different concentrations (50 mg/kg, 100 mg/kg and 200 mg/kg) were injected intraperitoneally (i.p.) at 15 min after SAH. The levels of TLR4, myeloid differentiation factor 88 (MyD88), nuclear factor- κB (NF-κB), Iba-1, CD86, CD206 and pro/anti-inflammation cytokines were measured by Western blotting and immunofluorescence staining at 24 h after SAH. SAH induction increased the protein levels of TLR4, pro-inflammation cytokines and proportion of M1 phenotype. Curcumin with 100 mg/kg treatment dramatically inhibited the release of pro-inflammatory mediators, and elevated the protein levels of anti-inflammatory cytokines and promoted microglia switch to M2. Meanwhile, curcumin treatment also decreased the expressions of TLR4, Myd88 and NF-κB at 24 h post SAH. TLR4 deficiency ameliorated brain water content, neurological deficit and reduced pro-inflammation cytokines after SAH. Moreover, curcumin treatment in tlr4-/- mice further induced M2 polarization, while had no statistic difference on brain water content and neurological score at 24 h post SAH. Our results indicated that curcumin treatment alleviated neuro-inflammation response through promoting microglia phenotype shift toward M2, and which might inhibiting TLR4/MyD88/NF-κB signaling pathway after SAH.